Mortalidade em povos indígenas no Brasil - LIMA, Janielle Ferreira de Brito (2019)
Objective: To analyze the trend of mortality in the indigenous population resident in Brazil in the time series from 1998 to 2016. Method: This is an ecological study of a temporal trend performed with data from the Death Certificates classified as "indigenous" in the item "race/color", registered throughout the national territory and made available by the Department of Information Technology of SUS. The data were collected in the last quarter of 2017 and the variables used were age, sex, place of death and basic cause of death. Data were processed using TabWin software and tabulation and analysis was performed using Microsoft Excel 2016 and Stata 14. Gross mortality rates and death rates by cause group were calculated. To evaluate the temporal trend of mortality data, the Prais-Winsten regression model was applied. Results: Gross indigenous mortality rates were low in all years of the series and there was a trend of increasing mortality. It was identified a high number of deaths of less than 1 year, 19% of the total recorded in the country, and in the North and Central-West regions this proportion approached that of the elderly. The main groups of causes of death were circulatory, followed by external ones. It is noteworthy that external causes were the main factors responsible for the deaths of young males and were more prevalent in the North, Midwest and South regions. Conclusion: Gross indigenous mortality rates were low when compared to the general population in the same period and the increasing tendency of mortality may be related to the worsening of the health situation of this population or to reflect a minimization of the underreporting of the deaths in the last years, emphasizing the need of special attention of the scholars of the area and of the health authorities for the evaluation of this indicator.